2017
DOI: 10.1080/13697137.2017.1386649
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in menopause and associated factors: a meta-analysis

Abstract: Menopause nearly adversely affects all components of MetS, and surgical menopause may lead to a higher incidence of MetS compared to natural menopause. HT with various preparations may have different effects on MetS components. These results may clarify the management of menopause-related MetS in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 89 publications
4
70
1
4
Order By: Relevance
“…This continuously increasing prevalence in women could be a result of menopause. Menopause was reported to have an association with an increased risk of MeS and it is affecting all of its components [ 48 ]. On the contrary, the decrease in the prevalence among men and women after the sixth decade of life could be due to survival bias, where people affected by MeS die at a comparatively younger age, which leads to a depletion in the older age categories of affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This continuously increasing prevalence in women could be a result of menopause. Menopause was reported to have an association with an increased risk of MeS and it is affecting all of its components [ 48 ]. On the contrary, the decrease in the prevalence among men and women after the sixth decade of life could be due to survival bias, where people affected by MeS die at a comparatively younger age, which leads to a depletion in the older age categories of affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The complete atrophy of ovarian function and severe estrogen deficiency , which are risk factors for cardiovascular diseases and diabetes , have caused many postmenopausal women to suffer from sequelae of menopause syndrome, including breast cancer and other gynecological cancers. It has been demonstrated that modifying individual estrogen metabolism profiles can prevent breast cancer in postmenopausal women .…”
mentioning
confidence: 99%
“…According to the results and for a better analysis of the obtained data, the subjects were divided in two groups, one with 25 (Fig. 6).…”
Section: Pth Vitamin D and Calciummentioning
confidence: 99%